Amyloid‐β activates NLRP3 inflammasomes by affecting microglial immunometabolism through the Syk‐AMPK pathway. Issue 5 (27th April 2022) - Jung, Eun Sun; Suh, Kyujin; Han, Jihui; Kim, Heyyoung; Kang, Hyung‐Sik; Choi, Won‐Seok; Mook‐Jung, Inhee
Abstract: Neuroinflammation is considered one of major factors in the pathogenesis of Alzheimer's disease (AD). In particular, inflammasome activation, including NLRP3 inflammasome in microglia, is regarded as fundamental for the pro‐inflammatory response of immune cells. However, the precise molecular mechanism through which the NLRP3 inflammasome is associated with AD pathologies remains unclear. Here, we show that amyloid‐β activates the NLRP3 inflammasome in microglia by activating Syk and inhibiting AMPK. Deactivated AMPK induces metabolic dysregulation, mitochondrial fragmentation, and reactive oxygen species formation, leading to the activation of the NLRP3 inflammasome. In addition, flufenamic acid (FA), a member of non‐steroidal anti‐inflammatory drugs, was found to effectively inhibit activation of the microglial NLRP3 inflammasome by regulating Syk and AMPK. Importantly, FA has marked therapeutic effects on major AD pathologies and memory function in vivo in microglia‐dependent way. All together, these findings demonstrate the molecular mechanism of microglial NLRP3 inflammasome activation by amyloid‐β, which acts as an important mediator of neuroinflammation. Also, we suggest that repurposing of FA for inhibiting microglial activation of the NLRP3 inflammasome is a potential treatment for AD. Abstract : In microglia, amyloid‐β caused Syk‐AMPK‐dependent mitochondrial dysfunction, which preceded NLRP3 inflammasome activation. Our study identified flufenamic acid (FA), a member of non‐steroidal anti‐inflammatory drugs, effectively inhibits the activation of the microglial NLRP3 inflammasome by regulating Syk and AMPK.